Mitochondrial and plastid genomes of the colonial green alga Gonium pectorale give insights into the origins of organelle DNA architecture within the Volvocales - Hamaji, Takashi; Smith, David R.; Noguchi, Hideki; Toyoda, Atsushi; Suzuki, Masahiro; Kawai-Toyooka, Hiroko; Fujiyama, Asao; Nishii, Ichiro; Marriage, Tara N.; Olson, Bradley J.; Nozaki, Hisayoshi (My University, 2013)
Volvocalean green algae have among the most diverse mitochondrial and plastid DNAs (mtDNAs and ptDNAs) from the eukaryotic domain. However, nearly all of the organelle genome data from this group are restricted to unicellular species, like Chlamydomonas reinhardtii, and presently only one multicellular species, the ~4,000-celled Volvox carteri, has had its organelle DNAs sequenced. The V. carteri organelle genomes are repeat rich, and the ptDNA is the largest plastome ever sequenced. Here, we present the complete mtDNA and ptDNA of the colonial volvocalean Gonium pectorale, which is comprised of ~16 cells and occupies a phylogenetic position closer to that of V. carteri than C. reinhardtii within the volvocine line. The mtDNA and ptDNA of G. pectorale are circular-mapping AT-rich molecules with respective lengths and coding densities of 16 and 222.6 kilobases and 73 and 44%. They share some features with the organelle DNAs of V. carteri, including palindromic repeats within the plastid compartment, but show more similarities with those of C. reinhardtii, such as a compact mtDNA architecture and relatively low organelle DNA intron contents. Overall, the G. pectorale organelle genomes raise several interesting questions about the origin of linear mitochondrial chromosomes within the Volvocales and the relationship between multicellularity and organelle genome expansion.
Keywords: Volvocalean green algae; Gonium pectorale; Organelle; DNA; Plastid genomes; Mitochondrial genomes